Identifikacija pasivnih strategij energijsko učinkovitega načrtovanja stavb, primernih za prenove obstoječih stavb - Lešnik Nedelko, Maja (Gradbeni vestnik, 2024)
Renovation of existing buildings has a significant potential for energy savings and GHG reductions, since only 0.4–1.2% of existing energy-inefficient buildings are renovated each year. Sustainable building design should contribute to reducing energy consumption, either by implementing passive design strategies or by using energy-efficient active systems powered by renewable energy sources. Depending on climate and location potentials, passive strategies can be classified into four bioclimatic strategies: heat retention, heat admission, heat exclusion, and heat dissipation. Approaches know as passive building design strategies are applicable not only to new building design but can also be used in the renovation of existing buildings. The aim of this study is therefore to identify different strategies and measures that are less frequently addressed in the scientific literature and could be used in future research on building renovation. The most frequently discussed are measures on the building envelope, transparent surfaces, shading and natural ventilation. Among the measures that often relate to other aspects of sustainability (environmental impacts, indoor comfort, etc.) and could be further investigated are the impact of the building shape, the layout of the interior spaces, cool roofs and facades, evaporative and radiative heat exchange. The results of the study can serve researchers to identify research gaps, as well as architects, builders and property owners, as they shed light on additional, less traditional options for retrofitting existing energy inefficient buildings.
Keywords: building renovation; energijska učinkovitost; energy efficiency; pasivne strategije načrtovanja stavb; passive building design strategies; prenove stavb; sustainable design; trajnostno načrtovanje